Do Brasil à Africa: resgatando valores através da Literatura, construindo uma sociedade multicultural e pluriétnica - Santos, Rubens Pereira dos [UNESP] (My University, 2012)
This paper addresses the role of literature in the construction of the new Brazilian society. The rescue of the cultural formation of identity values of the country, highlighting the African presence in various sectors of national life. In a project dedicated exclusively to children and young Brazilian students, aiming to demonstrate the multicultural and multiethnic existing in Brazilian culture. Literatures of Portuguese aid in the understanding of this reality.

Este texto aborda o papel da literatura na construção da nova sociedade brasileira. O resgate dos valores identitários na formação cultural do país, destacando a presença africana nos diversos setores da vida nacional. Num projeto voltado exclusivamente para crianças e jovens estudantes brasileiros, objetivando demonstrar a multiculturalidade e a plurietnia existentes na cultura brasileira. As literaturas de língua portuguesa auxiliam na compreensão dessa realidade.
From Brazil to Africa: values through literature, building a multicultural and multiethnic society
Keywords: Literature; Multicultural and multiethnic; Tales Angola; Africa; Brazil; Literatura; Multiculturalismo e plurietnia; Contos angolanos; Africa; Brasil